An analysis the training programme effectiveness in Ranhill Bersekutu Sdn Bhd by using Kirkpatrick model / Nordiana Mustapa Albakri and Siti Aisyah Mohd Fauzi - Mustapa Albakri, Nordiana; Mohd Fauzi, Siti Aisyah (Faculty of Business and Management, 2013)
In this term paper the researchers want to analyze the training programme effectiveness in the organization by using the Kirkpatrick model. This model or theory founded by Donald L Kirkpatrick from University of Wisconsin. Kirkpatrick Model had used four level or dimension for training evaluation which is reaction, learning, behaviour and result. Reaction is a first level in this model which is how the trainees felt about the training programme also their perception towards it. Followed by learning dimension which is in this level will measure the extent of trainees change attitude, improve knowledge and increase skills as a result of participating in the learning process. Third dimension is behaviour, this level is the extent of applied learning back in the job implementation. It can be performed formally or informally. The last dimension is result and this level the effect on the business environment by the trainee. In other words, the impact of the training either is meeting the targeted goals and objective or not. Training should be evaluated carefully to determine their effects, and to decide whether the organization should improve or discontinued the training programmed. In this study, the researcher have decided to use as 60 non- technical employees in Ranhill Bersekutu Sdn Bhd as a respondents to answer the questionnaires in order to analyze the training effectiveness by using the Kirkpatrick model. They recommended to evaluated the questionnaires based on the latest training programmed that they are attended.